2018
DOI: 10.1002/jctb.5545
|View full text |Cite
|
Sign up to set email alerts
|

Chronic impact of sulfamethoxazole: how does process kinetics relate to metabolic activity and composition of enriched nitrifying microbial culture?

Abstract: BACKGROUND This study investigated utilization kinetics of ammonia‐nitrogen induced by chronic sulfamethoxazole (SMX) exposure on biomass with an enriched nitrifying community. A lab‐scale activated sludge system was supplied with 100 mg COD L‐1 of peptone mixture and 50 mg N L‐1 of ammonia nitrogen at a SRT of 15 days. At steady‐state, the reactor was operated with additional daily SMX dosing of 50 mg L‐1 for 35 days. Profiles of oxygen uptake rates and nitrogen fractions obtained in respirometric/batch exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The same results were also reported in earlier studies. 1,26 It is interesting to note that the study by Pala-Ozkok, 54 where the experiment was conducted with conventional culture, also confirmed the same results, substantiating the suitability of the peptone mixture for this type of experimental evaluation. The table also lists the results of another study that was conducted with a COD/N ratio of 10 and only indicated a slight inhibition on the growth rate of AOBs and a variation of the endogenous decay coefficient, b H , between 0.10-0.20/day.…”
Section: Two-stage Nitrification Kineticssupporting
confidence: 58%
See 3 more Smart Citations
“…The same results were also reported in earlier studies. 1,26 It is interesting to note that the study by Pala-Ozkok, 54 where the experiment was conducted with conventional culture, also confirmed the same results, substantiating the suitability of the peptone mixture for this type of experimental evaluation. The table also lists the results of another study that was conducted with a COD/N ratio of 10 and only indicated a slight inhibition on the growth rate of AOBs and a variation of the endogenous decay coefficient, b H , between 0.10-0.20/day.…”
Section: Two-stage Nitrification Kineticssupporting
confidence: 58%
“…74,75 The study on the chronic impact of SMX basically involved observing the response of an enriched culture developed and sustained at steady-state to a continuous feeding of 50 mg/L of SMX for a period of 36 days, which was more than twice the sludge age selected for reactor operation. 26 Table 7 outlines the corresponding process kinetics obtained by means of model calibration of OUR profiles at different key steps along the observation period together with acute impact results of 50 mg/L SMX in this study. Run (2) related to the first day of SMX feeding, which replicated the acute exposure results in this study: competitive inhibition with markedly higher values for half saturation coefficients, K NH and K NO , and increased endogenous decay coefficients for both nitrifier fractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the simulation, the model was calibrated with the oxygen uptake rate (OUR) profiles generated with the selected wastewater. In previous studies, the standard deviation of the OUR measurements was assessed as 3%, a level, which is the same as that of COD analysis [48].…”
Section: Model Descriptionmentioning
confidence: 99%